2001
DOI: 10.1097/00129492-200109000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Electron Microscopic Study of the Surface Structure of Gold, Teflon, and Titanium Stapes Prostheses

Abstract: Because a certain roughness of the piston surface is necessary for the development of a stable membrane between the piston and the edge of the stapedotomy opening, the titanium prosthesis is considered to be the most suitable for stapes surgery of the three pistons examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…The Asterisk statistically significant difference. Theta statistically significant difference compared to hypoxic conditions with S53P4 granules implants used with bone contact are preferably slightly rough to provide a good attachment between the prosthesis and the surrounding tissue [34].…”
Section: Discussionmentioning
confidence: 96%
“…The Asterisk statistically significant difference. Theta statistically significant difference compared to hypoxic conditions with S53P4 granules implants used with bone contact are preferably slightly rough to provide a good attachment between the prosthesis and the surrounding tissue [34].…”
Section: Discussionmentioning
confidence: 96%
“…Dadurch besteht die Möglichkeit von aufsteigenden Infekten, die im Mittelohr zu entzündlichen Ergüssen führen können. Diese Ergebnisse korrelieren mit denen einer Studie von Kwok et al 2001, in der die Oberflächenstrukturen von verschiedenen Stapesprothesen aus Gold, Teflon und Titan ebenfalls elektronenmikroskopisch verglichen wurden. die Korrosionsbeständigkeit eines Materials eine wichtige Rolle.…”
Section: Diskussionunclassified
“…Hinsichtlich dieser potentiellen Milieuänderung der Implantatumgebung spielt z.B. Die Autoren kommen zu dem Schluß, daß Stapesprothesen aus Titan geeigneter sind [19]. Ebenso ist eine anti-mikrobielle Wirkung des Implantatmaterials wegen der fakultativen mikrobiellen Besiedelung von Vorteil [8].…”
Section: Diskussionunclassified
“…In their comparative electron microscopic study of the surface structure of gold, Teflon, and titanium stapes prostheses, Kwok et al (2001) concluded that the surface of the stapes prosthesis should show a certain roughness at the piston end to allow stable membrane attachment to the piston. The prosthesis should be roughened for better attachment or ossification in the loop area.…”
Section: What Should An Ideal Prosthesis Be?mentioning
confidence: 99%